Challenges Facing the Planning of Higher Education in Federal Capital Territory, Abuja, Nigeria - Ogunode Niyi Jacob (Jurnal Sinestesia, 2021)
Planning of Higher institutions in Nigeria and in Federal Capital Territory, Abuja, Nigeria has always been confronted with many challenges. This purpose of this study was to investigate the challenges facing planning of higher institutions in Federal Capital Territory, Abuja, Nigeria. A descriptive research method was adopted for the study. The total numbers of hundred (100) respondents were selected from various agencies and ministry of education using stratified and systematic sampling technique with the use questionnaires to collect information from respondents who participated in the study. The data collected were carefully analyzed using percentages supported by chi-square to represent the raw data in a meaningful manner. The questionnaire was validated by two lecturers from University of Abuja department of educational administration. Two research questions and one hypothesis were developed for the study. Test-retest reliability was employed for the study. Result collected and analyzed revealed that there is significant relationship between planning of higher institutions and challenges. This result also showed that political influence, political instability, inadequate data, inadequate fund to plan, pressure group, inadequate planning and poor capacity of planner are the challenges facing the planning of higher institutions. The paper recommends that the government should increase the budgetary allocation for educational planning in the country.